Outcome of fetal echogenic bowel: A systematic review and meta‐analysis. (21st February 2021) - D'Amico, Alice; Buca, Danilo; Rizzo, Giuseppe; Khalil, Asma; Silvi, Claudia; Makatsariya, Alexander; Nappi, Luigi; Liberati, Marco; D'Antonio, Francesco
Abstract: The main aim of this systematic review was to explore the outcome of fetuses with isolated echogenic bowel (EB) on antenatal ultrasound. Inclusion criteria were singleton pregnancies with isolated EB no associated major structural anomalies at the time of diagnosis. The outcomes observed were: chromosomal anomalies, cystic fibrosis (CF), associated structural anomalies detected only at follow‐up scans and at birth, regression during pregnancy, congenital infections, intra‐uterine (IUD), neonatal (NND) and perinatal (PND) death. Twenty‐five studies (12 971 fetuses) were included. Chromosomal anomalies occurred in 3.3% of the fetuses, mainly Trisomy 21 and aneuploidies involving the sex chromosomes. Cystic fibrosis occurred in 2.2%. Congenital infections affected 2.2%, mainly congenital Cytomegalovirus (CMV) infection. The majority of fetuses with EB experienced regression or disappearance of the EB at follow‐up scans. Associated anomalies were detected at a follow‐up scan in 1.8%. Associated anomalies were detected at birth and missed at ultrasound in 2.1% of cases. IUD occurred in 3.2% of cases while the corresponding figures for NND and PND were 0.4% and 3.1%. Fetuses with EB are at increased risk of adverse perinatal outcome, highlighting the need for a thorough antenatal management and postnatal follow‐up. Assessment during pregnancy and after birth should be performed in order to look for signs of fetal aneuploidy, congenital infections and associated structural anomalies.